The development and evaluation of mini-GEMs: a short, focused, online e-learning videos in geriatric medicine - Garside, Mark J.; Fisher, James M.; Blundell, Adrian G.; Gordon, Adam L. (Taylor & Francis, 2016)
Mini Geriatric E-Learning Modules (Mini-GEMs) are short, focused, e-learning videos on geriatric medicine topics, hosted on YouTube, which are targeted at junior doctors working with older people. This study aimed to explore how these resources are accessed and used. The authors analyzed the viewing data from 22 videos published over the first 18 months of the Mini-GEM project. We conducted a focus group of U.K. junior doctors considering their experiences with Mini-GEMS. The Mini-GEMs were viewed 10,291 times over 18 months, equating to 38,435 minutes of total viewing time. The average viewing time for each video was 3.85 minutes. Learners valued the brevity and focused nature of the Mini-GEMs and reported that they watched them in a variety of settings to supplement clinical experiences and consolidate learning. Watching the videos led to an increase in self-reported confidence in managing older patients. Mini-GEMs can effectively disseminate clinical teaching material to a wide audience. The videos are valued by junior doctors due to their accessibility and ease of use.